EFFECT OF DIFFERENT BENZOATE CONCENTRATIONS AND STORAGE ON SOME ISOLATED FUNGUS WHICH GROW ON ORANGE AND GRAPE FRUITE JUICES - Salah O.Ahmad (Mesopotamia Journal of Agriculture)
Isolation and purification of fungus which contaminated four species of citrus fruits which are orange , grape fruit , sweet lemon and sour lemon . Isolated fungus characterized , Penicillium digitatum , Althernaria citri and A.crassa used in this study because they were the most spread species in studied citrus fruits, The flasks stored for four weeks at ambient temperature with the presence of sodium benzoate with different concentrations. Values of PH and number of each of three fungus in all treatments were measured . Results showed that p.digitatum had the most spread in the four kinds of citrus fruits except orange , then A.citri which had the most spread in orange . The three species of fungus affected significantly (p < 0.05) in increasing of pH value with the absence of sodium benzoate especially in the last week of storage , but the addition of sodium benzoate with concentrations 0.05 and 0.1 % lead to still pH value in the average of standard treatment (at Zero week) , an increasing in the number of the three fungus with the increasing of storage period in 0.0% concentration of sodium benzoate in the two kinds of juices especially P. digitatum wherever the numbers are 239.5 and 203 ×104 spores / ml of orange and grape fruit juices respectively , but the addition of sodium benzoate especially at 0.05 and 0.1 % were significantly decreased the numbers of the three fungus.